2017
DOI: 10.1175/amsmonographs-d-16-0006.1
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Ice Nucleating Particles

Abstract: Ice particle formation in tropospheric clouds significantly changes cloud radiative and microphysical properties. Ice nucleation in the troposphere via homogeneous freezing occurs at temperatures lower than −38°C and relative humidity with respect to ice above 140%. In the absence of these conditions, ice formation can proceed via heterogeneous nucleation aided by aerosol particles known as ice nucleating particles (INPs). In this chapter, new developments in identifying the heterogeneous freezing mechanisms, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

35
807
2
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 687 publications
(991 citation statements)
references
References 278 publications
(353 reference statements)
35
807
2
5
Order By: Relevance
“…At water-saturated conditions, this is the first study to clearly show that during a SDE at the JFJ an increase in INPs is observed at 242 K. This agrees with the findings of an increase in INP concentrations observed during minor influence of Saharan dust (Boose et al, 2016b). We note that at 265 K an increase in immersion INPs at the JFJ was not observed during SDEs , indicating that dust contributes to ice nucleation at colder temperatures as has been previously suggested in numerous studies (see references in Hoose and Möhler, 2012;Murray et al, 2012;Kanji et al, 2017).…”
Section: Case 6 February 2015: Sdesupporting
confidence: 92%
“…At water-saturated conditions, this is the first study to clearly show that during a SDE at the JFJ an increase in INPs is observed at 242 K. This agrees with the findings of an increase in INP concentrations observed during minor influence of Saharan dust (Boose et al, 2016b). We note that at 265 K an increase in immersion INPs at the JFJ was not observed during SDEs , indicating that dust contributes to ice nucleation at colder temperatures as has been previously suggested in numerous studies (see references in Hoose and Möhler, 2012;Murray et al, 2012;Kanji et al, 2017).…”
Section: Case 6 February 2015: Sdesupporting
confidence: 92%
“…ciently understood (see, e.g., Vali et al, 2015;Kanji et al, 2017) and demand further investigation to accurately parameterize atmospheric ice formation in climate models Phillips et al, 2013). Laboratory measurements on well-characterized aerosol particles and ambient observations improve our understanding of atmospheric ice nucleation processes and INP abundance in the atmosphere.…”
mentioning
confidence: 99%
“…Further, Marcolli (2014) suggested that deposition nucleation might in fact be immersion freezing (or homogeneous freezing for T < 235 K) of water trapped in pores and cavities at water-subsaturated conditions. Which ice nucleation pathways exist and under what conditions they are relevant in the atmosphere is not fully understood, but has been speculated about and discussed (e.g., Kanji et al, 2017). It has been suggested that immersion mode is the dominant heterogeneous freezing pathway under mixed-phase cloud conditions (e.g., Ansmann et al, 2008;de Boer et al, 2011;Westbrook and Illingworth, 2011).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Combustion aerosols associated with BC might act as ice nucleating 30 particles (INPs) (Kanji et al, 2017) at the extreme cold temperatures found at high-altitude Arctic polar night, potentially leading to smaller, more numerous ice particles that precipitate less (Lohmann and Feichter, 2005), although some models Atmos. Chem.…”
Section: Discussion -Potential Aerosol Microphysical Mechanisms 20mentioning
confidence: 99%